Double adjuvanting strategy for peptide-based vaccines: trimethyl chitosan nanoparticles for lipopeptide delivery. (December 2016) - Marasini, Nirmal; Giddam, Ashwini K; Khalil, Zeinab G; Hussein, Waleed M; Capon, Robert J; Batzloff, Michael R; Good, Michael F; Toth, Istvan; Skwarczynski, Mariusz
Aim: To develop novel polymer-based nanoscale delivery system for lipopeptide-based vaccine against group A Streptococcus (GAS).Materials & methods: Four types of lipopeptide antigen-loaded polymeric nanoparticles (NP) were prepared. NP were accessed for their capacity to be taken up by dendritic cells; effect on dendritic cell maturation; ability to induce mucosal and systemic immunity; and capability to induce antibody responses that opsonize GAS bacteria.Results & discussion: The combination of adjuvanting properties of lipopeptides and dextran/trimethyl chitosan-based NP had a synergistic effect on humoral immunity, and the produced antibodies showed high opsonic activity against clinical GAS isolates.Conclusion: Biocompatible NP-bearing trimethyl chitosan and dextran are efficient as mucosal adjuvants for the intranasal delivery of lipopeptide-based vaccines.